Comparative analyses of phytochelatin synthase (PCS) genes in higher plants - Ertugrul Filiz; Ibrahim Adnan Saracoglu; Ibrahim Ilker Ozyigit; Bahattin Yalcin (Biotechnology & Biotechnological Equipment, 2019)
Plants employ various defence strategies to ameliorate the effects of heavy metal exposures, leading to re-establishment of metal homeostasis. One of the strategies includes the biosynthesis of main heavy metal detoxifying peptides phytochelatins (PCs) by phytochelatin synthase (PCS). In the present study, 14 PCS homologues were identified in the genomes of 10 selected plants. The size of these PCSs was 452–545 amino acid residues, with characteristic phytochelatin and phytochelatin_C domains. The N-terminal site of the proteins is highly conserved, whereas the C-terminal site is less conserved. Further, the present study also identified fully conserved Cys residues involved in heavy metal binding reported earlier. In addition, other preserved cysteines, with minor substitutions Cys(C)→Ser(S) or Tyr(Y) or Trp(W), were also identified in the PCS sequences that might be associated with metal binding. The reported catalytic triad residues from Arabidopsis, Cys56, His162 and Asp180, are all conserved at the respective sites of PCSs. A clear monocot/dicot separation was revealed by phylogenetic analysis and was further corroborated by the exon–intron organisations of the PCS genes. Moreover, gene ontology terms, co-expression network, cis-regulatory motif and miRNA analyses indicated that the complex as well as dynamic regulation of PCSs has significant involvement in different metabolic pathways associated with signalling, defence, stress and phytohormone, in addition to metal detoxification. Moreover, variations in protein structure are suggested to confer the functional divergence in PCS proteins.